ATR/BPN Regulation Policy Number 2 of 2024 Concerning the Moratorium on Protected Rice Field Land Reviewed from the Perspective of Legal Objectives (Benefit) - Dinda Shabila Fajrin; Heru Kuswanto (Universitas Merdeka Madiun, 2026)
Abstract Introduction to the Problem: The main problem in this study is the urgency of the moratorium policy for the establishment of the Regulation of the Ministry of Agrarian and Spatial Planning/National Land Agency (ATR/BPN) Number 2 of 2024 concerning Protected Rice Fields (LSD) and the moratorium policy is reviewed from the perspective of Utilization. Purpose/Study Objectives: This study aims to analyze the urgency of the moratorium policy for the stipulation of the Regulation of the Ministry of Agrarian and Spatial Planning/National Land Agency (ATR/BPN) Number 2 of 2024 concerning Protected Rice Fields (LSD) and the moratorium policy from the perspective of Utilization. Design/Methodology/Approach: This study uses normative legal research methods with a statutory approach (Statue approach) and a conceptual approach (Conceptual approach). Legal materials consist of primary legal materials, secondary and tertiary legal materials and qualitative descriptive analysis is carried out. Findings: The urgency of the moratorium policy on Protected Rice Fields (LSD) as stipulated in the Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency Number 2 of 2024 is not just an administrative instrument, but a manifestation of progressive legal policies that also provide preventive legal protection against the threat of land degradation, which in turn makes a real contribution to national food sovereignty. From the point of view of legal benefits, the policy of suspending Protected Agricultural Land can be seen as an action of state intervention to achieve a balance between development interests and the protection of agrarian resources. Paper Type: Research Article